Distance Measures for Surgical Process Models - Schumann, S.; Bühligen, U.; Neumuth, T. (Methods of Information in Medicine, 2013)
Background: The development of new resources, such as surgical techniques and approaches, results in continuous modification of surgery. To assess these modifications, it is necessary to use measures that quantify the impact of resources on surgical processes.Objectives: The objective of this work is to introduce and evaluate distance measurements that are able to represent differences in the courses of surgical interventions as processes.Methods: Hence, we present four different distance measures for surgical processes: the Jaccard distance, Levenshtein distance, Adjacency distance, and Graph matching distance. These measures are formally introduced and evaluated by applying them to clinical data sets from laparoscopic training in pediatric surgery.Results: We analyzed the distances of 450 surgical processes using these four measures with a focus on the difference in surgical processes performed by novices and by experienced surgeons. The Levenshtein and Adjacency distances were best suited to measure distances between surgical processes.Conclusion: The measurement of distances between surgical processes is necessary to estimate the benefit of new surgical techniques and strategies.
Keywords: Workflow; computer-assisted surgery; surgical process model; distance measures